Pt/C–LiCoO2 composites with ultralow Pt loadings as synergistic bifunctional electrocatalysts for oxygen reduction and evolution reactions. Issue 12 (3rd March 2016) - Su, Chao; Yang, Tao; Zhou, Wei; Wang, Wei; Xu, Xiaomin; Shao, Zongping
Abstract : A composite material with ultralow Pt loading showed excellent bifunctionality for the ORR and OER due to a synergistic effect. Abstract : Oxygen reduction and evolution reactions (ORR and OER) are of prime importance for many energy conversion and storage devices, such as regenerative fuel cells and rechargeable metal–air batteries. However, the sluggish kinetics of the ORR and OER strongly limit the efficiency and performance of these electrochemical systems and jeopardize the route of commercialization. Therefore, the design and development of bifunctional electrocatalysts with high activity for both the ORR and OER is challenging but urgent and crucial. Here, we took advantage of Pt/C and LiCoO2 with outstanding ORR activity and high intrinsic OER activity, respectively, to develop a composite material with ultralow Pt loading as a bifunctional catalyst for the ORR and OER in alkaline media. This catalyst was fabricated via simple ultrasonic mixing, exhibiting superb electrocatalytic activity and good stability. Its ORR activity is comparable to that of the commercial Pt/C catalyst and its OER activity is better than that of single LiCoO2, owing to the synergetic effect between Pt and LiCoO2, which has been demonstrated through the X-ray photoelectron spectroscopy (XPS) characterisation technique. Remarkably, surprisingly high ORR mass activity (2.04 A mgPt −1 at 0.8 V vs. RHE) and enhanced bifunctionality (Δ E = 0.91 V) were obtained for the Pt–LiCoO2 composite catalyst with a mass ratio of 1 : 49 for Pt/LiCoO2 . Our work opens up a new track to exploit highly efficient catalysts with reduced consumption of Pt, meanwhile maintaining the optimal catalytic activity and durability.